Síntese regiosseletiva de novas (4,5-diidropirazol-1-il)(-pirimidin-4-il)metanonas com potencial farmacológico - Camargo, Adriano Felin (2016)
This study shows the synthesis of five new 6-substituted 2-methylthio-4-pyrimidine carbohydrazides, aryl groups having such substituents (Ph, 4-FC6H4, 4-BrC6H4, 4-MeC6H4, 4-MeOC6H4) from the nucleophilic substitution of 6-substituted Ethyl 2-methylthiopyrimidine-4-carboxylate with hydrazine hydrochloride, with yields of 67- 78%. The cyclocondensation reactions of the carboidrazides, with 4-substituted 1,1,1-trifluorobut-3-en-2-ones led to the regioselective formation of twenty novel 3’- and 6-disubstituted (5-hydroxy-5-(trifluoromethyl)-4,5-dihydropyrazol-1-yl)(2-methylthiopyrimidin-4-yl) methanones, wherein the substituents on the pyrazoline (3') are Me, 2-furyl, Ph, 4-ClC6H4 and 4-MeOC6H4 in very good yields of 72-98%. The products obtained in this study were characterized by 1H and 13C NMR and low and high resolution mass spectrometry. The structure of representative compounds was confirmed by single crystal x-ray diffractometry.